2016
DOI: 10.1107/s2053230x1601298x
|View full text |Cite
|
Sign up to set email alerts
|

1.65 Å resolution structure of the AraC-family transcriptional activator ToxT fromVibrio cholerae

Abstract: ToxT is an AraC-family transcriptional activator protein that controls the expression of key virulence factors in Vibrio cholerae, the causative agent of cholera. ToxT directly activates the expression of the genes that encode the toxin-coregulated pilus and cholera toxin, and also positively auto-regulates its own expression from the tcp promoter. The crystal structure of ToxT has previously been solved at 1.9 Å resolution (PDB entry 3gbg). In this study, a crystal structure of ToxT at 1.65 Å resolution with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 41 publications
0
18
0
Order By: Relevance
“…ToxT has previously been shown to undergo proteolysis when V. cholerae is shifted to conditions that do not support virulence (i.e., from 30°C to 37°C, or when the pH increases from pH 6.5 to pH 8), but the specific proteases involved in this process are unknown (55). ToxT appears to be specifically cleaved in a recently structured region of the protein that lies in the N-terminal domain of the protein between amino acids 100 and 109 (56,57). Moreover, it has also been shown that the addition of the UFA linoleic acid to ToxT prevents its proteolysis (56), possibly by promoting the "closed" conformation of ToxT that is unable to bind to DNA or to activate gene expression (18).…”
Section: Discussionmentioning
confidence: 99%
“…ToxT has previously been shown to undergo proteolysis when V. cholerae is shifted to conditions that do not support virulence (i.e., from 30°C to 37°C, or when the pH increases from pH 6.5 to pH 8), but the specific proteases involved in this process are unknown (55). ToxT appears to be specifically cleaved in a recently structured region of the protein that lies in the N-terminal domain of the protein between amino acids 100 and 109 (56,57). Moreover, it has also been shown that the addition of the UFA linoleic acid to ToxT prevents its proteolysis (56), possibly by promoting the "closed" conformation of ToxT that is unable to bind to DNA or to activate gene expression (18).…”
Section: Discussionmentioning
confidence: 99%
“…The RD domain is very similar to that of the AraC but without the N-terminal loop. Instead, Li et al ( 2016 ) revealed a small α-helix (D101 to E110) in proximity of the RD to DBD linker. Mutational analysis in ToxT of Met103, Arg105 or Asn106 showed a threefold activation increase of the ctxA promoter, pointing out the important role of this small α-helix (Childers et al, 2007 ).…”
Section: The One-component System Regulatorsmentioning
confidence: 99%
“…The X-ray structure of ToxT revealed a 16-carbon monounsaturated fatty acid cis -palmitoleate bound in a pocket within the N-terminal domain2026, the homologous location as the arabinose-binding site within AraC27, a related protein for which the family is named. The fatty acid bridges the interface between the N-terminal dimerization domain and C-terminal DNA-binding domain of ToxT, suggesting a potential mechanism for fatty acid-mediated inhibition (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…This results in an “open” state, freeing the C-terminal domain to bind DNA and/or allowing the N-terminal domain to dimerize20. It has been suggested that this rearrangement may involve the flexible N-terminal loop between residues 108–11326. Therefore, ToxT is thought to exist in “closed” (inactive) and “open” (active) states20.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation